The electronic structure of transition-metal hydrides by nuclear magnetic resonance - Green, J (2017)
The platinum hydride complexes trans-Pt(PEt3)2HL have been prepared, where L is a carboxylato ligand. The carboxylato ligands were either substituted benzoato ligands i.e. o-NO2, m-NO2, p-NO2, o-Cl, m-Cl, p-Cl, o-Br, m-Br, p-Br, m-F, m-I, p-I, m-CH3, p-CH3, p-CH3O, m-(CH3)2N, p-(CH3)2N, p-CN, 3,5-(NO2)2, 2,5-(NO2)2 and 2,4,6-(NO2)3 or the substituted acetato ligands; CF3COO, CHCl2COO, CH2ClCOO, CH2(OC6H5)COO. The compounds were fully characterized by analysis, infrared and 1H nuclear magnetic resonance spectra, and, in the majority of cases, by molecular weight determinatons. The 1H nuclear magnetic resonance spectra of the complexes were studies in detail and, in particular, magnitudes of the chemical shift, τPt-H, and the platinum-hydrogen coupling constant, JPt-H, of the hydrido ligand were determined. The dependence of these quantities on concentration and solvent was examined. The platinum-hydrogen stretching frequency, νPt-H, was also determined. The parameters τPt-H, JPt-H, νPt-H and the pKa of the parent carboxylic acid HL were examined to see if there was any correlation between them. When one of the parameters being examined was pKa, three separate linear correlations were found, one for the ortho-substituted benzoato derivatives, one for the meta- and para- substituted benzoato derivatives and one for the substituted acetato derivatives. A plot between τPt-H and JPt-H shows two linear correlations namely for the substituted benzoato derivatives and for the substituted acetato derivatives. When the stretching frequency is being plotted against either τPt-H or JPt-H only one linear correlation is distinguishable. An attempt was made to interpret the observed variation in chemical shift in terms of the theory of Buckingham and Stephens for shielding in transition metal hydrides. It is concluded that the main cause of variation in shielding constant in the above complexes is change in the metal -hydrogen distance. An attempt to provide further evidence by a 2H nuclear magnetic resonance study of trans-Pt(PEt3)2DCl was inconclusive. The variation in the platinum-hydrogen coupling constant is discussed in terms of the molecular orbital formulation of the Fermi contact given by Pople and Santry. No conclusion may be drawn as to the relative importance of electronic factors which could cause variation in JPt-H in the above complexes, though it seems likely that variation in s-character of the metal hydrogen bond is probably significant. However consideration of JPt-H in a closely related series of platinum hydride complexes where L = NO3, I, Br, Cl, SCN, NO2, OCN, CN shows that they fall in the order of the position of L in the spectrochemical series. Although no rigorous theoretical significance may be attached to this fact it seems likely that factors other than the s-character of the metal-hydrogen bond are important in determining the variation of JPt-H in this series of complexes. The cobalt complexes Co(NH3)5L 2+ where L = C6H5COO, CF3COO, 3,5-(NO2)2C6H3COO, p-CH3OC6H4COO, p-NO2C6H4COO were prepared and their electronic spectra studied in order to ascertain their relation to the correlation found between JPt-H and the spectrochemical series for the acido ligands listed above. It was found that although they agreed roughly with the correlation between JPt-H and 1⁄ΔE where ΔE is the first ligand field band for the cobalt complexes, all the carboxylate complexes had the same ΔE, within experimental error, thus the variation in JPt-H from one carboxylate complex to another was in no way related to a change in ΔE. An attempt was made to estimate the shielding constant in platinum hydrides using the variation-perturbation technique formulated by Karplus and Kolker. Disagreement was found with the expression for shielding given by Karplus and Kolker. Use of the modified expression predicted a value of zero for the "paramagnetic" shielding of the hydrido ligand by the platinum d-electrons.